Challenges and Opportunities in Postharvest Horticulture Research and Training in Developing Countries – "The Case of Kenya”. - Mathooko, F. M.; Mutui, T. M. (My University, 2010)
The Kenyan horticulture industry has grown to become a major employer, contributor to food needs and foreign exchange earner. Horticulture is the second largest earner of foreign exchange after remittances from Kenyan Diaspora. In Kenya public sector horticultural research is conducted by public universities and the Kenya Agricultural Research Institute (KARI) as a public good. Challenges in postharvest (PH) horticulture research and training include inadequate funding (<5%), poor research infrastructure, shortage of trained PH manpower, low student enrolment, limited access to current literature and inadequate policies. Slow bureaucratic procedures in public institutions undermine their ability to respond to urgent farmers’ needs of low-cost PH technologies adaptable to different regions. Also, natural science researchers need better social science skills for technology transfer from laboratories to farms. Opportunities in PH research and training in Kenya include schools of agriculture in universities offering horticulture, postharvest physiology and technol¬ogy, food technology and processing. Activities for development of adequate PH capacity include training, education, extension and technology transfer. Because of very limited resources, PH research is directed towards specific problems and ‘knowledge-generation’. Kenya has a well-developed and dynamic private horti¬culture sector which presents an ideal investment opportunity with ready markets for produce. A successful approach to maximize PH research and training input would be development of programs with public-private partnerships having evolving roles. Moreover, the growing importance of environmental concerns presents opportunities and challenges for PH research. Rather than concentrating on isolated topics such as storage technology, emphasis on the whole PH value chain system can help in identifying bottlenecks, constraints and investment opportunities in order to increase the impact of PH research and training in horticulture.